Procedural Justice, Obligation to Obey, and Cooperation with Police in a Sample of Ghanaian Immigrants - Pryce, Daniel K. (Criminal justice and behavior, 2017)
Theory and research highlight the importance of procedural justice for inculcating people’s obligation to obey and willingness to cooperate with legal authorities, yet questions remain about the universality of these relationships across cultures and contexts. We examine the influence of procedural justice and other factors on Ghanaian immigrants’ obligation to obey and willingness to cooperate with police. The findings suggest that when police are perceived to behave in a procedurally just manner, people feel an increased obligation to obey their directives and willingness to cooperate with them. Perceived police effectiveness does not influence Ghanaian immigrants’ obligation to obey police, but is the most dominant factor in shaping their willingness to cooperate with police. Respondents’ views of police in Ghana did not influence obligation or cooperation. The implications of the results for theory development, empirical research, and policies intended to improve police-immigrant relations are discussed.